Observasi Mahasiswa/I IAT dalam Dakwah Qurani di Pesantren Modern Darul Ihsan - Teguh Perdana, Teguh Perdana; Habib Zikri; Muhammad Riyan Ramadhan; Airil Ihza Harefa; Annisa Sakinah; Nurul Natasya Nabilah; Humairah Humairah; Rizky Syah Putra (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the implementation of observational activities conducted by students of Qur’anic Sciences and Tafsir (IAT) in Qur’anic da’wah activities at Darul Ihsan Modern Islamic Boarding School. The focus of the study is directed at the forms of da’wah activities, the methods of delivering the material, and the responses of the students (santri) to the presence of university students acting as young preachers who are directly involved in the process of religious guidance within the boarding school environment. The method used in this study is a qualitative approach employing field observation techniques, in-depth interviews with relevant parties, and documentation as supporting research data. The results of the study indicate that IAT students are able to integrate their understanding of tafsir with a contextual communicative approach, making the Qur’anic material easier for students with different levels of ability to understand. The da’wah activities include thematic religious studies, tahsin and tahfiz of the Qur’an, Islamic discussions, and the development of students’ morals and character in their daily lives. The main supporting factors are the support from the boarding school authorities, a conducive learning environment, and the academic readiness of the students. Meanwhile, the obstacles encountered include limited time for implementing the activities and variations in students’ abilities to comprehend the material. In general, this observation provides valuable practical experience for students in applying the theory of Qur’anic da’wah while also strengthening the synergy between higher education institutions and Islamic boarding schools in developing sustainable Qur’an-based da’wah.